Developing a Compassionate Mind to Enhance Trauma-Focused CBT with an Adolescent Female: A Case Study. Issue 2 (17th May 2013) - Bowyer, Laura; Wallis, Jennifer; Lee, Deborah
Abstract : Background: Shame and disgust are often associated with posttraumatic stress disorder (PTSD) following interpersonal traumas such as sexual assault. It has been suggested that individuals with high levels of shame might do less well in standard cognitive behavioural (CBT) interventions.Aims: To see whether applying compassion-focused therapy and developing a compassionate mind can enhance trauma-focused CBT in an adolescent with high levels of shame and disgust the way it has been shown to within the adult population.Method: This single case study describes how trauma-focused CBT was enhanced by compassionate mind training. It details work using this approach with an adolescent female experiencing shame and disgust-based flashbacks. Treatment was provided for 20 sessions over 8 months. Symptoms of PTSD, depression and self-criticism, as well as the ability to self-soothe/reassure, were measured at assessment/start of treatment, mid- and end of treatment.Results: Clinically significant reductions in PTSD, depressive, shame and self-attacking symptoms were found between assessment and completion of treatment. Clinically significant increases in self-reassurance were also reported. Following treatment, symptoms of PTSD and depression were sub-clinical.Conclusion: This case study suggests that developing a compassionate mind alongside trauma-focused CBT may be beneficial to adolescents experiencing shame and disgust with consideration for the young person's level of development and personal circumstances.